Preliminary data on the development of emotion vocabulary in typically developing children (5–13 years) using an experimental psycholinguistic measure - Sturrock, Alexandra; Freed, Jenny (Frontiers in Psychology, 2023)
Introduction Vocabulary of emotion is integral to emotional development and emotional intelligence is associated with improved mental health outcomes. Many language disordered groups experience emotional difficulties; Developmental Language Disorders, Attention Deficit Hyperactivity Disorder and autism. However, (as in the case of autism) research tends to focus on assessing recognition of emotional states, rather than exploring labeling skills. Where labeling is assessed, measures have focused on early-acquired vocabulary (happy, sad, angry) or self/parent reporting. To date, no objective assessment has been made of vocabulary of emotion across childhood. Methods This study uses an experimental psycholinguistic measure, The Emotion Vocabulary: Expressive and Receptive ability measure (EVER) which includes two tasks (receptive vocabulary and word generation/expressive vocabulary). This measure has capacity to demonstrate vocabulary growth across age groups. 171 participants (5.0–13.11 years) completed The EVER Measure, alongside two closely matched standardized measures of basic language: BPVS (receptive vocabulary task) and CELF (word-association task). Assessments were completed online and en vivo (COVID testing restrictions dependent). Results As predicted, children’s accuracy increased on both receptive and expressive emotion vocabulary tasks, in line with age at time of testing. EVER scores were significantly predicted by age and correlated with matched basic language scores. Secondary analysis provided preliminary findings on age of acquisition for specific emotion vocabulary items. Discussion The findings consequently demonstrate proof of concept for the use of The EVER Measure in assessing emotional vocabulary across childhood. This study provides important preliminary data on generating and recognizing emotion labels across typical child development. Critically, it extends current knowledge on emotion vocabulary acquisition into middle childhood, where linguistic ability is relatively mature. As such, findings have implications for research with potential clinical application in the assessment of older children, with either language or emotional differences or both. Findings demonstrate the need for a standardized tool, and its potential application in research and clinical practice is explored. A large-scale study offering proof of concept and reliability of The EVER Measure is indicated.